Regular Physical Activity, Short-Term Exercise, Mental Health, and Well-Being Among University Students: The Results of an Online and a Laboratory Study - Herbert, Cornelia; Meixner, Friedrich; Wiebking, Christine; Gilg, Verena (Frontiers in Psychology, 2020)
The health benefits of regular physical activity and aerobic exercise are undisputed in the literature. The present series of pilot studies had two major objectives: a) examine mental health, well-being, and regular physical activity of university students and b) explore the potential health benefits of short-term aerobic exercise on university students in an online and a laboratory study. Mental health and well-being were measured before (Time 1, T1) and after (Time 2, T2) a six-week (online study) and two-week (laboratory study) low- to moderate-intensity aerobic exercise intervention. Mental health and well-being were assessed using standardized self-report measures of depression, anxiety, positive and negative affect, perceived stress and coping strategies, body dissatisfaction, and quality of life. The effects of the aerobic exercise were compared to a cognitive non-exercise control condition (online study), motor coordination exercise (laboratory study), and a waiting list (online and laboratory). A total of 185 university students were recruited from German universities at T1. Further, 74 (women: n = 67) students completed the six-week intervention. Similarly, 32 (women: n = 30) participants completed the two-week intervention (laboratory study). At T1, 36.6% of the students (women and men) reported experiencing depressive symptoms. 41.83% of them (women and men) had high levels of state anxiety. All the students reported experiencing stress (e.g., due to uncertainty related to factors such as their finances, job, and social relationships). At T1, regular physical activity was negatively correlated with self-reported depression, anxiety, and perceived psychosomatic stress and positively correlated with quality of life and positive affect. Among women, cardiovascular fitness (operationalized as resting heart rate variability) was negatively correlated with self-reported anxiety (state) and depression at T1 (laboratory study). The six-week aerobic exercise intervention resulted in significant improvements in self-reported depression, overall perceived stress, and perceived stress due to uncertainty. The present results confirm that there is a relationship between regular physical activity, cardiovascular fitness, mental health, and well-being among university students. They support the hypothesis that short-term aerobic exercise interventions can act as buffer against depression and perceived stress in university students after six weeks of aerobic exercise of low to moderate intensity.